Training workshop on performance-based assessment: feedback of the participants faculty - Piryani, Rano Mal; Piryani, Suneel (Journal of Chitwan Medical College, 2019)
Background: Performance-based assessment (PBA) concentrate on “Does” level of Miller’s Triangle Model of assessment and assess the ability of healthcare professionals to practice safely in different situations and context. It is essential to train faculty members how to conduct PBA. Methods: One-day training workshop on PBA was organized at Liaquat University of Medical & Health Sciences Jamshoro, Sindh Pakistan in November 08, 2017 with objective “participants learn to apply PBA tools in practice”. There were two sessions of training; session one covered basics, levels and tools of assessment and blueprinting for assessment and session two PBA and its tools. Tutorial, brainstorming and activity based small group work were methods utilized for the training. Feedback of the participants was taken on semi-structured questionnaire. Descriptive analysis was done using SPSS. Results: Twenty-two participants selected from basic, clinical, and dental sciences and nursing faculty. The participants rated workshop on scale of 1-10 (1=poor, 10=excellent) for usefulness of training (8.64 ± 1.62), content of training (8.27 ± 1.52), relevance of training & content (8.59 ± 1.40), facilitation of training (8.77 ± 1.34) and overall (8.77 ± 1.38). After training participants were very confident in developing blueprint for assessment (3.91±0.61), using mini-CEX (3.64±0.58), and confident using DOPS (3.63±0.73), MSF (3.55±0.74) and Portfolio (3.68±0.84). More than one third of the participants recommended to arrange more training workshop on different aspects of medical education. Conclusions: It was observed from feedback that participants realize the importance of PBA training and stress to have trainings for various aspects of health profession education.